Interplay between Inflammatory Responses and Lymphatic Vessels - Shin, Kihyuk (The Korean Association of Immunologists, 2014)
Lymphatic vessels are routes for leukocyte migration and fluid drainage. In addition to their passive roles in migration of leukocytes, increasing evidence indicates their active roles in immune regulation. Tissue inflammation rapidly induces lymphatic endothelial cell proliferation and chemokine production, thereby resulting in lymphangiogenesis. Furthermore, lymphatic endothelial cells induce T cell tolerance through various mechanisms. In this review, we focus on the current knowledge on how inflammatory cytokines affect lymphangiogenesis and the roles of lymphatic vessels in modulating immune responses.